2014
DOI: 10.1159/000366487
|View full text |Cite
|
Sign up to set email alerts
|

Is Excessive Electroencephalography Beta Activity Associated with Delinquent Behavior in Men with Attention-Deficit Hyperactivity Disorder Symptomatology?

Abstract: Background/Aims: The attention-deficit/hyperactivity disorder (ADHD) shows an increased prevalence in delinquents compared to the normal population. In recent studies, a subgroup of subjects with ADHD as well as a subgroup of delinquents displayed excessive electroencephalography (EEG) beta activity, which has been associated with antisocial behavior in ADHD children. We investigated whether delinquent behavior in adults with ADHD symptomatology is related to excessive beta activity. Methods: We compared the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…35,36 As probable reasons to increased beta activity in female have been considered the differences in brain structure, in skull thickness, and metabolic functioning. 37,38 Some studies using QEEG in male delinquent with ADHD, 39 male children with behavior problems and hyperactivity, 40 subjects of the both sexes with moderate intermittent explosive disorder, 41 male adults with ADHD and anger, 42 and in a community adolescent sample with externalizing psychopathology 43 had reported same findings as our research. Recently, Tuvblad et al 44 found positive correlation between increased of the frontal and parietal beta power and aggressive antisocial behavior in children.…”
Section: Discussionsupporting
confidence: 84%
“…35,36 As probable reasons to increased beta activity in female have been considered the differences in brain structure, in skull thickness, and metabolic functioning. 37,38 Some studies using QEEG in male delinquent with ADHD, 39 male children with behavior problems and hyperactivity, 40 subjects of the both sexes with moderate intermittent explosive disorder, 41 male adults with ADHD and anger, 42 and in a community adolescent sample with externalizing psychopathology 43 had reported same findings as our research. Recently, Tuvblad et al 44 found positive correlation between increased of the frontal and parietal beta power and aggressive antisocial behavior in children.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, three of the beta band connections of R.PCC with bilateral PFC and L.PHG, which showed hyperconnectivity in AUD, were also significantly associated with three of the BIS scores (except non-planning). Since beta oscillations are associated with AUD [155] and other externalizing traits [156], associations among beta band FC, impulsivity and hyperconnectivity in AUD are in line with the view that AUD is primarily a disinhibitory disorder [111] and may be related to neuronal hyperexcitability [108]. Interestingly, similar to the current findings, impulsivity factors ranked as the topmost predictors in our previous study on fMRI FC with the same set of participants [54].…”
Section: Heightened Impulsivity In Audsupporting
confidence: 90%
“…Furthermore, AUD individuals manifested relatively higher impulsivity and lower memory performance, in addition to aberrant neural connectivity (predominant hyperconnectivity) which were consistent with other behavioral/cognitive measures. Specifically, hyperconnectivity in three of the significant DMN connections in the beta band, the frequency which is frequently associated with externalizing disorders [155,156], were associated with increased impulsivity scores. These findings add support to the view that alcoholism can be considered as a disinhibitory disorder [109][110][111].…”
Section: Associations Among Aud Fc Impulsivity and Neurocognitionmentioning
confidence: 97%
“…Studies indicate that an excessive beta frequencies in children with ADHD was believed to cause restlessness, anxiety, distractibility and impulsivity [26]- [29]. It was also speculatively suggested that a high beta was an indication of comorbidity.…”
Section: Resultsmentioning
confidence: 99%